KONTRIBUSI KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN SPIN PADA ATLET TENIS MEJA PTM MALAY SPORT CENTER - Mulyadi, Deden; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the reality in the field, especially during the author's observations about the spin ability of the PTM Malay Sport Center table tennis athletes, it is because in every exercise or competition it looks less than optimal, which results in a decrease in technical abilities, especially in the spin technique they have. This often happens because of a lack of physical abilities. This means that physical abilities and spin abilities are related. This research aims to: determine the contribution of arm muscle strength to the spin ability of the PTM Malay Sport Center table tennis athletes. The population in this study were all PTM Malay Table Tennis athletes, amounting to 7 male athletes. Sampling with total sampling technique, by taking the entire population to be the research sample. The instruments in this study were push-ups to measure the strength of the arm and shoulder muscles and the ability to top spin. The data obtained were analyzed using product moment correlation. Contribution is made by using a determinant coefficient. Based on the results of the research described in the previous chapters, the following conclusions can be drawn: there is a contribution of arm muscle strength to the spin ability of the PTM Malay Sport Center table tennis athletes by 4.88%.Key Words: Arm Muscle Strength, Spin Ability